2016
DOI: 10.1007/s11596-016-1599-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between p53 polymorphism at codon 72 and recurrent spontaneous abortion

Abstract: p53 gene plays an important role in apoptosis, which is necessary for successful invasion of trophoblast cells. The change from an arginine (Arg) to a proline (Pro) at codon 72 can influence the biological activity of p53, which predisposes to an increased risk of recurrent spontaneous abortion (RSA). In order to investigate the association between p53 polymorphism at codon 72 and RSA, we conducted this meta-analysis. Pubmed, Embase and Web of science were used to identify the eligible studies. Odds ratio (OR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…These results are consistent with five meta-analyses examining the relationship between p53 p.Arg72Pro variant and RPL [11,[36][37][38][39]. Tang et al, 2011 analyzed four case control studies and concluded that women with the homozygous Pro/Pro genotype had an increased risk of RPL [11].…”
Section: Discussionsupporting
confidence: 63%
“…These results are consistent with five meta-analyses examining the relationship between p53 p.Arg72Pro variant and RPL [11,[36][37][38][39]. Tang et al, 2011 analyzed four case control studies and concluded that women with the homozygous Pro/Pro genotype had an increased risk of RPL [11].…”
Section: Discussionsupporting
confidence: 63%
“…A number of studies have demonstrated an association between genetic variants and the risk of RSA (27)(28)(29)(30). VEGF is among the established regulators of angiogenesis during pregnancy and has been associated with RSA (31,32).…”
Section: Resultsmentioning
confidence: 99%
“…19,20 Furthermore, studies have found that some genes that regulate cell proliferation, invasion, and migration are associated with susceptibility to miscarriage; for example, H19 and p53 gene polymorphisms. 8,21 These studies suggest that TINCR gene polymorphisms may be associated with recurrent miscarriage. However, there have been no previous studies on the association between TINCR polymorphism rs2288947 A > G and recurrent miscarriage; therefore, we conducted this study.…”
Section: Introductionmentioning
confidence: 88%
“…Recently, studies have found that genetic variation in TINCR was associated with a variety of diseases, such as the SNP rs2288947, which contributed to the susceptibility and progression of colorectal cancer and susceptibility to gastric cancer . Furthermore, studies have found that some genes that regulate cell proliferation, invasion, and migration are associated with susceptibility to miscarriage; for example, H19 and p53 gene polymorphisms . These studies suggest that TINCR gene polymorphisms may be associated with recurrent miscarriage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation